Kepercayaan Konsumen Memediasi Omnichannel Integration Quality Pada Niat Pembelian Kembali di PT Pegadaian (Persero) Medan - Britto E Simatupang; Romindo Megawati Pasaribu; Agus Simanjuntak; Herry D.S Pasaribu; Vinsensius Matondang (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
Companies that are able to provide integrated services will increase interactions with companies with the aim of creating a consistent product experience for consumers. This is referred to as the channel method omnichannel marketing which integrates digital services (application usage) with physical (in-store) to consumers to have experience and convenience in transacting with the company. This study aims to provide empirical evidence regarding the configuration of service channels and integrated interactions on the repurchase intention of PT Pegadaian Branch Madya Medan's service products. Furthermore, the trust variable is used as a mediating variable to increase consumers' desire to repurchase. By using the technique purposive sampling used criteria in taking research samples; obtained as many as 103 valid responses through random data collection to respondents using google forms. Analysis Structural Equation Modeling (SEM) used to test the measurement and structural models through Smart-PLS 3.0. The results of this study indicate that (1) the variable configuration of the service channel and integrated channel has a significant effect on trust; (2) service channel configuration has a significant effect on repurchase intention, (3) but the integrated interaction variable has no significant effect on repurchase intention. Meanwhile, (4) the trust variable significantly mediates the service channel configuration variable and the integrated interaction on repurchase intention. Empirical and theoretical contributions are discussed in the discussion of this research